Dynamic simulation of granular filtration - Leong, Lee Man (2016)
Much experimental and numerical research works have been conducted in the attempt to gain deeper understanding of the hydrodynamics in a granular filter bed and improving the filtration process by means of reducing head loss, improving particle removal and optimizing backwash. Most numerical studies conducted developed simulation models considering the flow across an entire filter bed. Little has been done to evaluate the filtration process from a pore-scale simulation. To address the research gap, this study was conducted to develop a robust numerical model to emulate the deep bed filtration process, in order to predict the head loss incurred and the collector efficiency based on the flow across a single collector to a good extent. The study also developed and investigated the efficacy of engineered shapes in attenuating the head loss incurred during rapid filtration run while achieving similar or greater particle removal. The numerical model, developed using COMSOL, provided simulation results that closely approximates empirical values when accounting for head loss and particle removal due to direct interception. Simulated values for particle removal due to sedimentation deviated slightly from empirical values. Miniature interior rectangular slots were integrated into the design of the engineered shape to act as flow channels. The design managed to considerably reduce the head loss incurred, with the extent of the reduction achieved depending on the width of slotted flow channels. Simulation results attained for collector efficiency suggests that a similar degree of particle removal was attained with the engineered shape. Further works on optimizing the numerical model through the application of a better shape for the representation of the granular media and minimizing the gaps near the wall of the simulation domain are suggested. Experimental analysis could also be done on the filtration process using filter media resembling the design on the engineered grain.